AN EMPIRICAL INVESTIGATION ON DIGITAL STRATEGIES ADOPTED BY HOMESTAYS IN ERNAKULAM DISTRICT, KERALA - Amlin David; J. Clement Sudhahar and Praising Linijah (International Journal of Mechanical Engineering and Technology, 2019)
Tourism industry plays a major role in development of the state of Kerala. The adoption of digital techniques in all the industries has only increased the competition among all industrial sectors. Homestays are the backbone of Kerala Tourism said the Central Minister for tourism India Mr. Alphonse Joseph Kannathanam in Kerala that too after the occurrence of the great flood which effected the tourism industry in the State. Homestay business is one of the most popular businesses in Ernakulam district due to its emergence as a major hub for tourism in the State. In the research the authors analyze the various Digital Marketing techniques which are being practiced by the Home stays in Ernakulam District. The authors found that online hotel booking portals are vital for being competitive in the Homestay industry. The authors tested the service quality strategies and its connection to e service satisfaction. It was statistically found that Facebook was still the most popular social media platform by the Home stay owners in Ernakulam. The result also showed that social media too has a major role in overall business development. The authors were also able to understand that most of the digital marketing techniques such as Email Marketing and Blogs were not familiar to the Homestay owners